Biochemical characteristics and antioxidant activity of crude and purified sulfated polysaccharides from Gracilaria fisheri. Issue 3 (3rd March 2016) - Imjongjairak, Siriluck; Ratanakhanokchai, Khanok; Laohakunjit, Natta; Tachaapaikoon, Chakrit; Pason, Patthra; Waeonukul, Rattiya
Abstract: Sulfated polysaccharides (SPs) from Gracilaria fisheri of Thailand, which were extracted in low-temperature (25 °C) water showed the highest content of phenolic compounds compared with those extracted at high temperature (55 °C). Crude SP antioxidant activity was evaluated by measuring the DPPH free radical scavenging effect which is directly related to the level of phenolic compounds. The sulfate content, total sugar, and SPs yield were also directly related to the extraction temperature. All extracts contained galactose as a major monosaccharide. High antioxidant activity of crude SP, positively correlated with the phenolic compound contents ( R 2 = 0.996) contributed by the existence of sulfate groups and phenolic compounds. In purified SP, F1 fraction exhibited strong radical scavenging ability, but it was not significantly different compared to crude SP extracted at 25 °C. This indicated that the appropriate density and distribution of sulfate groups in the SP extract showed the best antioxidant activity. Graphical abstract: : Sulfated polysaccharides(SPs) of G. fisheri extracted with water at 25 °C is a new source of natural antioxidants, and purified SP fractions have potential antioxidant activity.